A phase field approach for the fully coupled thermo-electro-mechanical dynamics of nanoscale ferroelectric actuators. (20th April 2018) - Wang, Dan; Du, Haoyuan; Wang, Linxiang; Melnik, Roderick
Abstract: The fully coupled thermo-electro-mechanical properties of nanoscale ferroelectric actuators are investigated by a phase field model. Firstly, the thermal effect is incorporated into the commonly-used phase field model for ferroelectric materials in a thermodynamic consistent way and the governing equation for the temperature field is derived. Afterwards, the modified model is numerically implemented to study a selected prototype of the ferroelectric actuators, where strain associated with electric field-induced non-180° domain switching is employed. The temperature variation and energy flow in the actuation process are presented, which enhances our understanding of the working mechanism of the actuators. Furthermore, the influences of the input voltage frequency and the thermal boundary condition on the temperature variation are demonstrated and carefully discussed in the context of thermal management for real applications.